Phenotypic lag in macroconidia of N. crassa his-3+ transsformants and its implication in estimation of nuclear ratios - K Pitchaimani; R Maheshwari (Fungal Genetics Reports, 2000)
A majority of prototrophic macroconidia of two of the three histidine transformants of Neurospora crassa tested required histidine for germination. This condition led to an underestimation of the proportion of his-3+ macroconidia in the samples and wronged the estimation of ratio of his-3+/ his-3 nuclei by direct plating method. To correctly estimate nuclear ratio, a sample of colonies from histidine-supplemented plating medium was transferred to histidine drop-out slants and the proportion of auxotrophic and prototrophic colonies was determined from their growth response. The amino acid requirement by prototrophic macroconidia was not specific, was limited to colony formation and was not due to low endogenous content of amino acids.